\(\cfrac{x+y}{3a-b}=\cfrac{y+z}{3b-c}=\cfrac{z+x}{3c-a} \) হলে, দেখাই যে, \(\cfrac{x+y+z}{a+b+c}=\cfrac{ax+by+cz}{a^2+b^2+c^2}\)


ধরি, \(\cfrac{x+y}{3a-b}=\cfrac{y+z}{3b-c}=\cfrac{z+x}{3c-a}=k \) (যেখানে \(k≠0)\)

\(∴x+y=k(3a-b) -----(i)\)
\( y+z=k(3b-c) -----(ii) \)
এবং, \(z+x=k(3c-a) ---(iii)\)

\((i),(ii)\) এবং \((iii)\) নং সমীকরনের উভয়পক্ষ যোগ করে পাই
\(x+y+y+z+z+x=k(3a-b+3b-c+3c-a)\)
বা, \(2(x+y+z)=2k(a+b+c) \)
বা, \((x+y+z)=k(a+b+c)----(iv)\)
বা, \(\cfrac{x+y+z}{a+b+c}=k \)

\((iv)\) নং থেকে \((i)\) নং সমীকরন বিয়োগ করে পাই
\((x+y+z)-(x+y)= k(a+b+c)-k(3a-b) \)
বা, \(y=k(a+b+c-3a+b)\)
বা, \(y=k(c+2b-2a)\)

\((iv)\) নং থেকে \((ii)\) নং সমীকরন বিয়োগ করে পাই
\((x+y+z)-(y+z)= k(a+b+c)-k(3b-c) \)
বা, \(x=k(a+b+c-3b+c)\)
বা, \(x=k(a+2c-2b)\)

\((iv)\) নং থেকে \((iii)\) নং সমীকরন বিয়োগ করে পাই
\((x+y+z)-(z+x)= k(a+b+c)-k(3c-a) \)
বা, \(y=k(a+b+c-3c+a)\)
বা, \(y=k(b+2a-2c)\)

\(∴ \cfrac{ax+by+cz}{a^2+b^2+c^2} \)
\(=\cfrac{ak(a+2c-2b)+bk(b+2a-2c)+ck(c+2b-2a)}{(a^2+b^2+c^2 )}\)
\(=\cfrac{k(a^2+2ac-2ab+b^2+2ab-2bc+c^2+2bc-2ac)}{a^2+b^2+c^2})\)
\(=\cfrac{k(a^2+b^2+c^2 )}{(a^2+b^2+c^2 )}\)
\(=k\)

\(∴\cfrac{x+y+z}{a+b+c}=\cfrac{ax+by+cz}{a^2+b^2+c^2} \)
[∵উভয়ের মানই \(k\)](প্রমানিত)

Similar Questions